Higher education in Egypt (Reviews of national policies for education, 2010)
In recent years, the Government of Egypt has driven major reforms for modernising the country. However, Egypt’s higher education system has remained largely unchanged and without fundamental reform of the sector the country will face difficulties in improving its competitiveness. This independent review of Egypt’s higher education system focuses on areas in need of attention by policy makers and stakeholders, including system steering and institutional governance; student access to higher education; educational quality and effectiveness; research, development and innovation; and finance. It contains an analysis of the system and valuable recommendations which, taken together, represent a major programme of structural and cultural reform of Egyptian higher education over the decade to 2020.